Effects of Cyclic Loading on the Mechanical Properties of Mature Bedding Shale - Yintong Guo; Chunhe Yang; Lei Wang; Feng Xu (Advances in Civil Engineering)
We investigated the mechanical properties of mature bedding shale under cyclic loading conditions, with an application to the design of hydraulic fracturing in shale gas wells. Laboratory experiments were conducted on shale samples under two principal loading orientations. Testing results showed that accumulated fatigue damage occurs in a three-stage process. Analysis of fatigue damage at different maximum stress levels shows that fatigue life increases as a power-law function with maximum stress decreasing. And the maximum stress significantly affects the fatigue life. Further, the elastic part of shale rock deformation was recovered in the unloading process, whereas the irreversible deformation remained. The irreversible deformation, growth trend, and accumulation of the total fatigue were directly related to the fatigue damage. This process can be divided into 3 stages: an initial damage stage, a constant velocity damage stage, and an accelerated damage stage, which accounted for about one-third of the fatigue damage. Shale rock is a nonhomogeneous material, and the bedding is well developed. Its fatigue life differs greatly in two principal loading orientations, even under the same loading conditions. All of these drawn conclusions are of great importance for design of hydraulic fracturing in shale gas wells.